The Effect of Service Quality (Reliability, Responsiveness, Assurance, Empathy, & Tangible) and Cost Perception on Satisfaction and Positive Word of Mouth of UKDW Faculty of Medicine Students - Hardini, Renny; Santoso, Singgih (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
Improving the standards of higher education services is crucial for attracting and retaining students, particularly at the Faculty of Medicine at UKDW. The objective of this study is to examine how perceptions of cost and service quality (reliability, responsiveness, assurance, empathy, and tangibles) influence student satisfaction and positive word-of-mouth promotion. This study employs an explanatory design and quantitative methodology. Data analysis was conducted using multiple linear regression and Structural Equation Modeling (SEM), obtained from active students in their second semester or higher via a questionnaire. The results indicate that student satisfaction is significantly influenced by all dimensions of service quality and cost perceptions. Additionally, as a sign of loyalty to the institution, student satisfaction acts as a strong mediating factor in promoting positive word of mouth. These results highlight the importance of implementing cost perception management and service development initiatives based on student needs to enhance the reputation and competitiveness of medical higher education institutions. In conclusion, a positive learning environment and natural institutional promotion depend on high-quality services and reasonable tuition fees.